Competitive balance and demand for football: A review of the literature - Tsjalle van der Burg (Hochschule Pforzheim, 2022)
In European men's club football, competitive balance is decreasing, and therefore uncertainty of outcome too. The empirical studies do not give a clear unanimous answer to the question whether this decrease leads to lower utility for the fans, and so to lower welfare, hence this critical review of the literature. Three types of uncertainty of outcome have been distinguished in the literature: short-term, seasonal, and long-term, with possible different dimensions within one type. The paper argues that it is justified to interpret the literature in the following way: a decrease in one or two types of uncertainty of outcome, or a certain more specific dimension, can lead to serious reductions in welfare, while the conclusion may be different for other types or dimensions. Several studies suggest that a decrease in competitive balance has no effect on welfare, or just a small effect, as long as the competitive balance remains above some minimum level (or range) whereas once the competitive balance is below the minimum level, any further decrease in it results in serious reductions in welfare. Taking these and other points into account, the conclusion of the review is that it is highly plausible that the present level of competitive balance is below the welfare-maximising level in most competitions at least, and any further decrease in competitive balance will seriously reduce welfare.
Keywords: 330; Fußball; Profisport; Sportveranstaltung; Wettbewerb; Nachfrage; Europa